DEPICTION OF BIRRUL WALIDAIN VOICED BY CHILDREN THROUGH POEMS OF 2000 - Syahruni Junaid; Sumarni Sumarni (UIN Alauddin Makassar, 2021)
This research discussed the depiction of Birrul Walidain expressed by children through poems after 2000 which aimed to find out the diction expressed how they love their parents and the tendency of changes among the poems during the range of time the poems were written. This research used the indicators of birrul walidain by Yunahar Ilyas as the theory. The researcher applied the descriptive qualitative method and used note-taking as the instrument to find out valid data. The researcher found that all the elements of birrul walidain presented in the poems written by children posted on family friend poems website and also, the researcher found changes regard to the poems shows changes regard to birrul walidain indicators among the years the poems were written.